PEACE BUILDING BASED ON THE LOCAL WISDOM (The study of Phenomenology-Ethnography in the Society of Islamic Relegion, Cristian, Hinduism at Balun Village, Turi Subdistric Lamongan District ) - Ahmad Zakki Fuad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2016)
The differences between of religion and belief in a particular community is usually will show a conflict between followers of religions. It has become a fact of history that can not be ignored. whereas, if it is returned on the purpose of religion itself, of course, conflict, hostility, war is something contradictory. All of true religion have aimed to creat the objectives of the human being. Such as, through the realization of harmony in social life. Religion suggests the importance of building a good attitude in the society besides spiritual rites. It was a union of two aspects relations between vertical and horizontal. Rural Prototype communities in the region which have three religions and places of worship side by side in Balun Village Turi subdistric Lamongan district. Balun one of the village have multicultur and plural in the society over the years never happened conflicts religious. Because of it, the researcher suppose to searh how is the social construction of the religious, in the harmony and how is the process of establishing the values of harmony, religious rites and cultural activities that involve people of the different religions. Phenomenological etnography approach in this research through the data sources that are grouping refers to the stratification. Social startifikasi in used in this research according to Pitrim A.Sorokin and Max Weber theories were the strata of society devided into some group based on the standard such as; respectable, power and authority, knowledge and income . then From this theory the researcher devided the society into four group. The first are the figures of Islamic religious, Christian, Hindu. Second the committee of mosgue, Church and Temple Board, third local goverment staff, educators, teachers in all religius. The fourth regular community; farmers , factory workers. Based on analyzed of phenomenological ethnography, the researchers found the result of the study, these are the social construction of the religious community, harmony and the establishment of the values in the harmony guided by the respectable each others in ideology, respectable to the hereditary tradition, expressing happiness had shown when other communities in religious rituals celebration, gave awards to other religious communities as well as a sense of togetherness reflected in any religious activities and social activities in Balun village. The Harmony foundation in the application as